An Unlikely Retirement: The 2017 Las Vegas Massacre as an Exercise in Project-Based Deviant Leisure. Issue 4 (November 2018) - Arntfield, Michael; Williams, D. J.
In recent years, homicide scholarship has been the beneficiary of an increasingly interdisciplinary framework that has come to include a leisure science perspective in attempting to explain murder as a pleasure-seeking avocation for offenders. In this article, the authors employ a leisure-based approach to the Las Vegas Massacre as a foundational case study on multiple murder as project-based deviant leisure. Homicidal leisure-based projects, as suggested here, may also amount to intuitive extensions of other higher-risk hobbies known as edgework. A leisure approach to understanding some forms of multiple murder provides valuable new insights while also integrating important tradition.